Neonatal anthropometric indicators of infant growth and mortality in Burkina Faso - Mamadou Bountogo; Ali Sié; Alphonse Zakane; Guillaume Compaoré; Thierry Ouédraogo; Elodie Lebas; Kieran Sunanda O'Brien; Thomas M Lietman; Catherine E Oldenburg (Cambridge University Press, 2024)
Abstract Objective: Most evidence supporting screening for undernutrition is for children aged 6-59 months. However, the highest risk of mortality and highest incidence of wasting occurs in the first 6 months of life. We evaluated relationships between neonatal anthropometric indicators, including birth weight, weight-for-age Z-score (WAZ), weight-for-length Z-score (WLZ), length-for-age Z-score (LAZ) and mid-upper arm circumference (MUAC) and mortality and growth at 6 months of age among infants in Burkina Faso. Design: Data arose from a randomised controlled trial evaluating neonatal azithromycin administration for the prevention of child mortality. We evaluated relationships between baseline anthropometric measures and mortality, wasting (WLZ < -2), stunting (LAZ < -2) and underweight (WAZ < -2) at 6 months of age were estimated using logistic regression models adjusted for the child's age and sex. Setting: Five regions of Burkina Faso. Participants: Infants aged 8-27 d followed until 6 months of age. Results: Of 21 832 infants enrolled in the trial, 7·9 % were low birth weight (<2500 g), 13·3 % were wasted, 7·7 % were stunted and 7·4 % were underweight at enrolment. All anthropometric deficits were associated with mortality by 6 months of age, with WAZ the strongest predictor (WAZ < -2 to ≥ -3 at enrolment v. WAZ ≥ -2: adjusted OR, 3·91, 95 % CI, 2·21, 6·56). Low WAZ was also associated with wasting, stunting, and underweight at 6 months. Conclusions: Interventions for identifying infants at highest risk of mortality and growth failure should consider WAZ as part of their screening protocol.